Uma análise institucionalista do Instituto de Defesa do Consumidor – PROCON/AM - Abreu, Rafael Freire de (Brasil, 2025)
Institutional Economics, an area of economics that emphasizes the role of institutions in economic organization and functioning, presents various ideas throughout its evolution about what institutions are and how they affect the economy. This can be observed in its two main branches: the Old Institutional Economics, with Veblen, Commons, and Mitchell, which criticizes the neoclassical view of rationality and incorporates historical and social influences; and the New Institutional Economics, with North, Coase, and Williamson, which focuses on transaction costs and the impact of institutions on economic development. Within this context, PROCON AMAZONAS plays a role in protecting and defending Amazonian consumers, exercising a regulatory function that influences consumer relations and challenges the conventional economic theory of a self-regulating market. The objective of this study is to conduct an institutional analysis of PROCON/AM and thereby answer the following question: “What is the purpose of PROCON?”